A kind of antibacterial high-barrier fruit and vegetable fresh-keeping film and preparation method thereof
By ball milling the chitosan powder with sodium hydroxide, adding sodium chloroacetate and sodium iodide, after quaternization modification and silver-loading treatment, and then intercalation modification with montmorillonite to form a composite film, the existing fruit and vegetable plastic wrap is solved, and the problem that is difficult to meet at the same time in terms of barrier properties, antibacterial properties and harmlessness to the human body is achieved, and efficient freshness preservation and food safety of fruits and vegetables are achieved.
Patent Information
- Application Number
- CN202510127066.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing fruit and vegetable plastic wrap is difficult to meet the barrier properties, antibacterial properties and harmlessness to the human body, resulting in poor preservation effects of fruit and vegetable, and may contain additives that are harmful to the human body.
A high-bacterial antibacterial and high-barrier fruit and vegetable fresh-preservation film is adopted. The preparation method includes ball milling of chitosan powder and sodium hydroxide, adding sodium chloroacetate and sodium iodide, quaternization modification and silver-loading treatment, and then intercalation modification with montmorillonite to form a composite film.
The film has excellent antibacterial properties and barrier properties, significantly extends the shelf life of fruits and vegetables, reduces food waste and losses, and is harmless to the human body.
Smart Images

Figure CN119751942A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fruit and vegetable preservation, and relates to an antibacterial and high-barrier fruit and vegetable preservation film and a preparation method thereof. Background Art
[0002] In the food industry, fruit and vegetable preservation has always been a key research area. With the improvement of people's living standards and the change of consumption concepts, the requirements for the freshness, taste, nutritional value and safety of fruits and vegetables are getting higher and higher. However, after picking, fruits and vegetables are prone to quality degradation and rot and deterioration due to factors such as respiration, water evaporation, and microbial contamination. This not only affects the edible value of fruits and vegetables, but also brings huge economic losses to the fruit and vegetable industry.
[0003] At present, the main methods of preserving fruits and vegetables include low-temperature storage, modified atmosphere packaging, chemical preservatives, etc. Low-temperature storage prolongs the shelf life by reducing the respiration and microbial activity of fruits and vegetables, but long-term low temperature may cause the texture of fruits and vegetables to become soft, the taste to deteriorate, and even cause chilling damage; modified atmosphere packaging inhibits the respiration and microbial growth of fruits and vegetables by adjusting the gas composition in the package, but the selection of packaging materials, the regulation of gas ratios, and packaging cost considerations are all factors that restrict its widespread application; although chemical preservatives have a significant preservation effect, they may leave chemical substances that are harmful to the human body and affect food safety.
[0004] In terms of fruit and vegetable cling film, traditional cling film mainly serves to isolate air and prevent water evaporation, but it has obvious shortcomings in terms of preservation effect. On the one hand, traditional cling film has limited barrier properties against gas and water, and it is difficult to effectively inhibit the respiration and microbial growth of fruits and vegetables; on the other hand, traditional cling film lacks antibacterial function and cannot effectively prevent microbial contamination. In addition, some traditional cling film materials may contain additives that are harmful to the human body, such as plasticizers, and long-term use may pose a potential threat to human health.
[0005] In recent years, as people's awareness of food safety and environmental protection increases, the requirements for fruit and vegetable cling film are getting higher and higher. The ideal fruit and vegetable cling film should have excellent barrier properties, antibacterial properties, air permeability and harmlessness to the human body. However, most of the fruit and vegetable cling films on the market currently cannot meet these requirements at the same time. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an antibacterial and high-barrier fruit and vegetable fresh-keeping film and a preparation method thereof. The composite film prepared by the present invention has excellent antibacterial and barrier properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, the preparation method comprising:
[0009] (I) ball-milling chitosan powder and sodium hydroxide to obtain a mixture, adding sodium chloroacetate and sodium iodide to the mixture for a second ball-milling to obtain carboxymethyl chitosan; then, quaternizing the carboxymethyl chitosan with dimethyl diallyl ammonium chloride to obtain quaternized carboxymethyl chitosan;
[0010] (II) dispersing the quaternized carboxymethyl chitosan obtained in step (I) in deionized water to obtain a chitosan solution, dripping a silver ammonia solution into the chitosan solution under stirring and water bath heating conditions, and continuing to mix, stir and heat to react after all the silver ammonia solution has been dripped in, and then dialyzing and freeze-drying to obtain silver-loaded chitosan;
[0011] (III) dispersing the silver-loaded chitosan obtained in step (II) in deionized water to obtain a silver-loaded chitosan solution, adding montmorillonite to the silver-loaded chitosan solution, mixing, stirring and heating, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0012] (IV) The polylactic acid, the intercalated montmorillonite obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the antibacterial and high-barrier fruit and vegetable fresh-keeping film.
[0013] The antibacterial high-barrier fruit and vegetable fresh-keeping film prepared by the present invention has excellent antibacterial properties and barrier properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables, and reduce food waste and loss. Among them, silver-loaded chitosan can destroy the cell structure of bacteria and interfere with its metabolic process, thereby effectively inhibiting the growth of common food spoilage bacteria such as Escherichia coli and Staphylococcus aureus. At the same time, silver ions have broad-spectrum antibacterial properties and are not easy to develop drug resistance, giving the composite film excellent antibacterial properties and effectively extending the shelf life of fruits and vegetables. The present invention intercalates montmorillonite through silver-loaded chitosan, further improving the interlamellar spacing of montmorillonite, thereby forming a more compact and effective barrier barrier in the composite film, reducing oxygen, moisture, etc. from passing through the composite film, and significantly improving the barrier properties of the composite film.
[0014] The invention sequentially performs carboxymethyl modification and quaternization modification on chitosan to obtain quaternized carboxymethyl chitosan, then uses silver ammonia solution as a precursor and quaternized carboxymethyl chitosan as a reducing agent and a stabilizer to prepare silver-loaded chitosan; finally, the silver-loaded chitosan is used to perform intercalation modification on montmorillonite, and after ion exchange between organic cations of dimethyl diallyl ammonium chloride grafted on the silver-loaded chitosan and inorganic cations between montmorillonite layers, the cation part is attached to the montmorillonite sheet, and the organic part is attached to the montmorillonite sheet. Stay in the interlayer, as the chitosan molecular chain enters the interlayer of montmorillonite, the interlayer distance of montmorillonite increases, the structure becomes looser, the porosity is higher, and some layers are peeled off, so that the silver-loaded chitosan is fixedly loaded between the layers of montmorillonite. This structure not only maintains the original barrier properties of montmorillonite, but also enhances the barrier capacity of the composite film to gases (such as oxygen, carbon dioxide) and water through the interaction of chitosan molecular chains, which can effectively extend the shelf life of fruits and vegetables and prevent moisture from invading and causing the performance of the composite film to deteriorate. In addition, the introduction of silver-loaded chitosan also improves the thermal and chemical stability of montmorillonite. The functional groups in the chitosan molecular chain can form hydrogen bonds with the hydroxyl groups on the surface of montmorillonite, which enhances the interlayer interaction force and makes the intercalation structure more stable; at the same time, the presence of silver nanoparticles also plays a catalytic stabilizing role, further improving the overall stability of the intercalated montmorillonite. This improvement in stability enables the intercalated montmorillonite to still exert good barrier properties under extreme environmental conditions (such as high temperature and high humidity).
[0015] Chitosan is mainly composed of random copolymerization of N-acetylglucosamine and glucosamine units. The particularity of this structure gives chitosan a series of significant functional properties, such as excellent biocompatibility, non-toxicity, good biodegradability and antibacterial activity, but unmodified chitosan is only water-soluble and antibacterial under acidic conditions, which limits its scope of application. The present invention uses sodium chloroacetate to carboxymethylate chitosan, aiming to introduce hydrophilic carboxymethyl functional groups, thereby improving the water solubility and reactivity of chitosan. Compared with chitosan, carboxymethyl chitosan not only retains the original biocompatibility and degradability of chitosan, but also gives it certain antibacterial and reactivity, laying the foundation for subsequent quaternary ammonium modification; at the same time, the chain structure of carboxymethyl chitosan is more flexible, the concentration of chelating groups is larger, and its ability to chelate metal particles is stronger than chitosan, so it can be used as a reducing agent and stabilizer for subsequent silver nanoparticles.
[0016] The present invention uses sodium chloroacetate as a carboxymethyl modification agent and sodium iodide as a catalyst, and adopts a mechanochemical method to induce a chemical reaction, thereby introducing a carboxymethyl functional group on the chitosan molecular chain, and the introduction of the carboxymethyl functional group greatly improves the solubility of chitosan. The present invention adopts mechanical ball milling to promote the alkalization reaction and the carboxymethylation reaction. During the ball milling process, the ball milling medium and the reaction material are subjected to the combined force of rotation and revolution in the ball mill, so that the centrifugal acceleration of the ball milling medium can reach 10-20g; at the same time, the pressure between the ball milling medium and the ball mill can reach 5-6 times of the weight of the ball milling medium itself. When the chitosan molecule is subjected to a strong mechanical force of the ball milling medium, the impact force and shear force of the chitosan particles will destroy the crystal structure in the molecule. During the ball milling alkalization process, sodium hydroxide can better enter the interior of the chitosan molecule, thereby achieving the effect of alkalization expansion. At the same time, during the carboxymethylation reaction, as the hydrogen bonds within and between chitosan molecules are broken by external mechanical force, the hydroxyl and amino groups within the chitosan molecules are exposed to the outside, thereby providing an attack target for the carboxymethyl groups in the system and promoting the occurrence of the carboxymethylation reaction.
[0017] In addition to the carboxymethyl functional group, the carboxymethyl chitosan also has free hydroxyl groups and amino groups that are not completely reacted during carboxymethylation, so that the carboxymethyl chitosan has enough reactive functional groups. On this basis, the present invention adopts dimethyl diallyl ammonium chloride to perform quaternization modification on the carboxymethyl chitosan. The quaternization modification not only retains and improves the water solubility of the carboxymethyl chitosan, but also grafts quaternary ammonium salt cations on the carboxymethyl chitosan molecular chain through the graft copolymerization reaction of dimethyl diallyl ammonium chloride and carboxymethyl chitosan. On the one hand, the water solubility of the chitosan can be further improved. The quaternary ammonium functional group is grafted into the chitosan molecular chain through the graft copolymerization reaction. The introduction of the quaternary ammonium functional group weakens the hydrogen bonding effect in the chitosan molecule, destroys its crystal structure, makes the distance between the molecular chains larger, and the molecules are in a "loose" state, which is conducive to the approach and penetration of water molecules. Therefore, chitosan modified with quaternary ammonium salts can be dissolved under both acidic and alkaline conditions, and the solution has good stability, does not change color or degrade; on the other hand, quaternary ammonium modification not only improves the water solubility of chitosan, but also significantly enhances its antibacterial properties. The quaternary ammonium functional group carries a stronger positive charge, which can interact with the negative charge on the surface of bacterial cells, destroy the integrity of the bacterial cell wall, and cause bacterial death; in addition, the high charge density of the quaternary ammonium modified chitosan enables it to form a polycationic electrolyte, which reacts with the acidic macromolecules produced on the surface of bacterial cells to form a polyelectrolyte complex, further inhibiting the growth of bacteria.
[0018] The present invention particularly preferably uses dimethyldiallyl ammonium chloride to quaternize carboxymethyl chitosan. The dimethyldiallyl ammonium chloride copolymer belongs to an organic cation. In the subsequent montmorillonite intercalation modification process, the dimethyldiallyl ammonium chloride copolymer can exchange cations with inorganic cations between montmorillonite layers to enter the interlayers of montmorillonite and open the interlayers of montmorillonite. The montmorillonite with enlarged interlayer spacing is used as a carrier of silver-loaded chitosan to achieve load fixation of the silver-loaded chitosan, and can effectively prevent the agglomeration of the silver-loaded chitosan and silver nanoparticles loaded between the interlayers.
[0019] Silver nanoparticles have excellent antibacterial properties and have obvious inhibitory effects on various microorganisms such as bacteria and fungi. Its antibacterial mechanism involves destroying cell membrane permeability, affecting bacterial cell phospholipid and protein synthesis, etc., and can effectively kill or inhibit the growth of pathogens. Compared with traditional antibiotics, silver nanoparticles are not easy to cause microorganisms to develop drug resistance, which enables silver nanoparticles to maintain a stable antibacterial effect in long-term use. The present invention uses quaternized carboxymethyl chitosan to coat and fix silver nanoparticles, further enhancing the application efficiency and safety of silver nanoparticles. On the one hand, quaternized carboxymethyl chitosan can form a smooth, transparent, flexible and breathable film, which helps to prevent the penetration and growth of microorganisms, and synergizes with silver nanoparticles to significantly improve the antibacterial effect. At the same time, the carboxymethyl functional groups on the quaternized carboxymethyl chitosan molecular chain can also chelate with metal ions, further enhancing its antibacterial ability. On the other hand, although silver nanoparticles have excellent antibacterial properties, their potential cytotoxicity limits their direct application. The present invention uses quaternized carboxymethyl chitosan to coat silver nanoparticles, which can effectively reduce the cytotoxicity of silver nanoparticles and improve their biosafety; at the same time, through the coating of quaternized carboxymethyl chitosan, the slow release of silver ions can be achieved, the antibacterial action time can be extended, and the stability of silver nanoparticles can be improved, preventing their aggregation and precipitation, and maintaining long-term antibacterial activity.
[0020] As a layered silicate mineral, montmorillonite has a very high specific surface area and interlayer adsorption capacity. Through the intercalation modification of silver-loaded chitosan, the interlayer spacing of montmorillonite is expanded and the interlayer structure is effectively regulated. This intercalation structure not only improves the dispersion uniformity of intercalated montmorillonite in the composite film, but also enhances its interfacial bonding force with the polymer matrix. At the same time, intercalated montmorillonite, as an inorganic nanofiller, can significantly enhance the rigidity and heat resistance of the composite film.
[0021] As a preferred technical solution of the present invention, in step (I), the mass ratio of the chitosan powder to sodium hydroxide is 1:(3.5-4.5), for example, it can be 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4 or 1:4.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] The present invention particularly limits the mass ratio of chitosan powder and sodium hydroxide to 1:(3.5-4.5), and along with the increase of sodium hydroxide consumption, the substitution degree of the carboxymethyl functional group of the product obtained after subsequent carboxymethylation modification presents a variation trend of first increasing and then decreasing. In the alkalization reaction process, sodium hydroxide plays the role of alkalization expansion, and when the consumption of sodium hydroxide is lower than the lower limit of the range defined by the present invention, it does not have a good alkalization expansion effect, affects the subsequent carboxymethylation reaction, and causes the substitution degree of the carboxymethyl functional group of the product to be lower. Along with the increase of sodium hydroxide consumption, the active center formed also increases thereupon, the structure of chitosan is destroyed, and the particles expand, so that it can better react with sodium chloroacetate, so that the carboxymethylation reaction is fully carried out, and therefore, the substitution degree of the carboxymethyl functional group of the product is gradually improved. When the amount of sodium hydroxide used exceeds the upper limit of the range defined in the present invention, not only mass transfer is hindered, but also the excess sodium hydroxide will neutralize a portion of the sodium chloroacetate, affecting the progress of the carboxymethylation reaction, resulting in a decrease in the reaction efficiency of the carboxymethylation reaction. At the same time, since the generated by-products are wrapped in the surface layer of the chitosan, it is difficult for the sodium chloroacetate to contact the inside of the chitosan, which hinders the progress of the carboxymethylation reaction to a certain extent. Therefore, the degree of substitution of the carboxymethyl functional group of the product is reduced.
[0023] In some optional examples, the rotation speed of the primary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional examples, the time for the first ball milling is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional examples, the mass ratio of the chitosan powder to sodium chloroacetate is 1:(3~4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] The reaction of sodium chloroacetate and chitosan mainly occurs on the amino group on the chitosan molecular chain. Under alkaline conditions, sodium chloroacetate ionizes chloroacetate ion, which has nucleophilicity and can attack the amino group on the chitosan molecular chain to form the carbon anion of the intermediate. Subsequently, the intermediate undergoes intramolecular or intermolecular rearrangement to generate carboxymethyl chitosan and release chloride ions. Chitosan itself is a polymer material with poor hydrophilicity. Through carboxymethylation modification, hydrophilic carboxymethyl groups can be introduced to improve its hydrophilicity. The amount of sodium chloroacetate has a significant effect on the hydrophilicity of carboxymethyl chitosan. The present invention particularly limits the mass ratio of chitosan powder and sodium chloroacetate to 1: (3-4). When the amount of sodium chloroacetate is within the numerical range defined by the present invention, the carboxymethylation reaction of chitosan is carried out more completely, and the number of carboxymethyl groups introduced in the chitosan molecule is moderate, so that the carboxymethyl chitosan not only maintains the original excellent properties of chitosan, but also has good hydrophilicity. When the amount of sodium chloroacetate is lower than the lower limit of the range defined in the present invention, the carboxymethylation reaction is not completely carried out, and the number of carboxymethyl functional groups introduced into the chitosan molecule is insufficient, so that the hydrophilicity of the carboxymethyl chitosan is limited, and it is difficult to meet the requirements of the fruit and vegetable fresh-keeping film for hydrophilicity. When the amount of sodium chloroacetate exceeds the upper limit of the range defined in the present invention, it will cause excessive carboxymethylation reaction, and too many carboxymethyl functional groups will be introduced into the chitosan molecule, which will not only destroy the original molecular structure of chitosan and reduce its mechanical strength, but also make the hydrophilicity of the carboxymethyl chitosan too strong, causing the composite film to be easily deformed by water absorption during use, affecting the fresh-keeping effect.
[0027] In some optional examples, the mass ratio of sodium chloroacetate to sodium iodide is 1:(0.5~0.7), for example, it can be 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58, 1:0.6, 1:0.62, 1:0.64, 1:0.66, 1:0.68 or 1:0.7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional examples, the rotation speed of the secondary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] The invention particularly limits the rotation speed of the secondary ball milling to 500-600 rpm, and as the rotation speed of the ball milling increases, the substitution degree of the carboxymethyl functional group of the product shows a trend of first increasing and then decreasing. When the rotation speed of the ball mill is within the range of 500-600 rpm, accelerating the rotation speed of the ball milling can increase the collision probability and the number of collisions of the chitosan powder, sodium hydroxide, sodium chloroacetate and sodium iodide, and when the mechanical force is large enough, the stress generated instantly by the chitosan powder far exceeds its mechanical strength, and then the powder particles are broken, the specific surface area is increased, the contact of the chitosan powder with the sodium hydroxide, sodium chloroacetate and sodium iodide is promoted, and the reaction rate of the carboxymethyl reaction is increased, so the substitution degree of the carboxymethyl functional group of the product is gradually increased. When the ball mill speed exceeds 600rpm, the excessively fast speed causes the contact time between the reaction materials and the ball milling medium to be too short. At the same time, the particle size of the chitosan powder cannot be further reduced after reaching the limit, and the tiny particles will agglomerate into secondary particles under the action of surface energy, van der Waals force and electrostatic force. When the ball mill speed exceeds 600rpm, the agglomeration rate of the tiny particles will exceed the generation rate of the tiny particles. At this time, a large number of secondary particles will be generated in the reaction system, resulting in a sharp decrease in the specific surface area of the material and a rapid decrease in the reaction rate, which ultimately leads to a decrease in the degree of substitution of the carboxymethyl functional group of the product.
[0030] In some optional embodiments, the secondary ball milling time is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the preparation process of the carboxymethyl chitosan further comprises:
[0032] After the secondary ball milling, a solid product is obtained, and the solid product is uniformly mixed with deionized water to obtain a product solution. A hydrochloric acid solution with a mass fraction of 8-10wt% is added to the product solution to adjust the pH value of the product solution to 7; then, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan, which can be, for example, 8.0wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt% or 10.0wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] As a preferred technical solution of the present invention, in step (I), the quaternized carboxymethyl chitosan is prepared by the following method:
[0034] The carboxymethyl chitosan is dissolved in deionized water and mixed evenly to obtain a carboxymethyl chitosan solution; under continuous stirring and water bath heating conditions, a dimethyl diallyl ammonium chloride solution is added dropwise to the carboxymethyl chitosan solution, and after the dimethyl diallyl ammonium chloride solution is completely added dropwise, the mixture is continuously stirred and heated to obtain a reaction product; acetone is added to the reaction product, and white floccules are generated after mixing, and then the mixture is filtered, washed and dried to obtain the quaternized carboxymethyl chitosan.
[0035] As a preferred technical solution of the present invention, the concentration of carboxymethyl chitosan in the carboxymethyl chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional examples, the mass fraction of the dimethyldiallylammonium chloride solution is 50-60wt%, for example, it can be 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt% or 60wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, during the process of adding the dimethyldiallylammonium chloride solution, the temperature of the water bath heating is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:(0.6~0.7), for example, it can be 1:0.6, 1:0.61, 1:0.62, 1:0.63, 1:0.64, 1:0.65, 1:0.66, 1:0.67, 1:0.68, 1:0.69 or 1:0.7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] The present invention adopts dimethyl diallyl ammonium chloride as quaternization modification reagent, reacts with the carboxymethyl functional group on the carboxymethyl chitosan molecular chain, forms quaternary ammonium salt structure, this structure not only enhances the water solubility of carboxymethyl chitosan, also endows it with stronger positive charge, thereby improves its antibacterial property. The present invention particularly limits the mass ratio of carboxymethyl chitosan and dimethyl diallyl ammonium chloride to be 1:(0.6~0.7), adds appropriate amount of dimethyl diallyl ammonium chloride can ensure that the functional group on the carboxymethyl chitosan molecular chain obtains more uniform quaternization modification, avoids the carboxymethyl chitosan molecular chain destruction or crosslinking caused by overreaction, and the quaternization modification caused by insufficient reaction is not thorough. When the consumption of dimethyl diallyl ammonium chloride is lower than the lower limit of the range defined by the present invention, it will cause quaternization reaction to be insufficient, the functional group on the carboxymethyl chitosan molecular chain fails to be fully converted into quaternary ammonium salt structure, makes the positive charge of the product finally obtained insufficient, is difficult to effectively combine with bacterial cell wall, thereby reduces the antibacterial activity of the product. When the consumption of dimethyldiallyl ammonium chloride exceeds the upper limit of the range limited by the present invention, although the positive charge of carboxymethyl chitosan can be further increased, due to the steric hindrance of dimethyldiallyl ammonium chloride, it is more inclined to copolymerization, and too many quaternary ammonium salt functional groups can cause the interaction between molecular chains to be enhanced, and the homopolymerization reaction of dimethyldiallyl ammonium chloride monomer is accelerated to form a cross-linked structure, which hinders the generation of graft copolymerization between dimethyldiallyl ammonium chloride and carboxymethyl chitosan to a certain extent, thereby affecting the dispersibility and solubility of the final product in water. In addition, excessive dimethyldiallyl ammonium chloride may also cause cytotoxicity, causing potential harm to organisms, and at the same time, antibacterial performance will not continue to enhance with the increase of dimethyldiallyl ammonium chloride consumption, and after reaching a certain concentration, antibacterial performance will tend to saturation or even slightly decline.
[0040] In some optional examples, after all the dimethyldiallylammonium chloride solution has been added dropwise, mixing and stirring are continued under heating conditions at 50-60° C. in a water bath for 20-30 min, for example, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] In some optional examples, the volume ratio of the reaction product to the acetone is 1:(1-1.2), for example, 1:1.0, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] As a preferred technical solution of the present invention, in step (II), the silver ammonia solution is prepared by the following method:
[0043] Under stirring conditions, sodium hydroxide solution is added to the silver nitrate solution to react and generate a silver oxide suspension containing a black silver oxide precipitate. Ammonia solution is added dropwise to the silver oxide suspension until the black silver oxide precipitate is completely dissolved to obtain a clear silver ammonia solution.
[0044] In some optional examples, the mass fraction of the silver nitrate solution is 3~5wt%, for example, it can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the mass fraction of the sodium hydroxide solution is 2-4wt%, for example, it can be 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt% or 4.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the mass ratio of silver nitrate in the silver nitrate solution to sodium hydroxide in the sodium hydroxide solution is 1:(0.5~0.8), for example, it can be 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75 or 1:0.8, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the concentration of the aqueous ammonia solution is 1~3wt%, for example, it can be 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, in step (II), the concentration of quaternized carboxymethyl chitosan in the chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] In some optional examples, during the process of adding the silver ammonia solution, the temperature of the water bath heating is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] The present invention particularly limits the water bath heating temperature to 70-80°C. When the reaction temperature is lower than 70°C, the reduction rate of silver ions by quaternized carboxymethyl chitosan is low, and only a small amount of silver seeds grow into silver nanoparticles. As the temperature increases, on the one hand, the growth rate of silver seeds into silver nanoparticles is accelerated, and on the other hand, a large amount of silver ions in the mixed solution system form crystal nuclei, further generate silver nanoparticles, and increase the silver loading of the product. When the reaction temperature is higher than 80°C, the silver nanoparticles generated in the solution will continuously collide due to the intensification of Brownian motion, the silver nanoparticles will cluster, and a silver single substance with a larger particle size will be generated, which cannot be evenly loaded on the quaternized carboxymethyl chitosan, resulting in a decrease in the silver loading of the product.
[0051] In some optional examples, the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:(0.6~0.7), for example, it can be 1:0.6, 1:0.61, 1:0.62, 1:0.63, 1:0.64, 1:0.65, 1:0.66, 1:0.67, 1:0.68, 1:0.69 or 1:0.7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] The present invention particularly limits the mass ratio of quaternized carboxymethyl chitosan to silver nitrate to 1:(0.6-0.7). When the amount of silver nitrate is lower than the lower limit of the range defined by the present invention, the number of silver nanoparticles generated on the quaternized carboxymethyl chitosan is small and unevenly distributed. As a broad-spectrum antibacterial agent, the antibacterial performance of the silver nanoparticles mainly depends on the interaction between the silver nanoparticles and the bacterial cell membrane, and the ability to interfere with the metabolic process of the bacteria after entering the interior of the bacteria. If the content of the silver nanoparticles is insufficient, the growth and reproduction of the bacteria cannot be effectively inhibited. In addition, the uneven distribution of the silver nanoparticles will lead to a lack of sufficient antibacterial effect in some areas. With the increase of the amount of silver nitrate, the generation amount of the silver nanoparticles gradually increases, and the antibacterial performance of the silver-loaded chitosan is significantly enhanced.
[0053] In addition, the amount of silver nitrate used will directly affect the particle size of the generated silver nanoparticles. The formation of silver nanoparticles includes two processes: nucleation and crystal growth. In the nucleation process, a certain degree of supersaturation is required to overcome the surface energy barrier. The crystal growth process is a process in which the newly reduced silver element is adsorbed on the surface of the original crystal nucleus and grows on the basis of the previous nucleation. Both processes will undergo liquid phase reduction reactions, but nucleation is the main process in the early stage and crystal growth is the main process in the later stage. In the nucleation process, the concentration of silver nanoparticles exceeds the critical concentration value, the system reaches a supersaturated state, and silver nanoparticles can precipitate from the reaction system. When the amount of silver nitrate is too small, the silver ion concentration is low, the supersaturation of silver nanoparticles is relatively low, the crystal nucleation rate is greater than the crystal growth rate, and the particle size of the generated silver nanoparticles is small. When the amount of silver nitrate is increased, the silver ion concentration in the reaction system increases, the supersaturation continues to increase, the crystal growth rate is greater than the crystal nucleation rate, and the particle size of the generated silver nanoparticles is larger.
[0054] Therefore, when the amount of silver nitrate used exceeds the upper limit of the range defined by the present invention, large-diameter silver nanoparticles will be formed. At the same time, unreacted silver ions gather on the surface of the silver nanoparticles and undergo a reduction reaction on the surface of the silver nanoparticles, so that the large-diameter silver nanoparticles are further agglomerated to generate secondary particles with a larger particle size but a smaller specific surface area. The secondary particles will affect the full contact between the silver nanoparticles and the bacteria, thereby affecting the full play of its antibacterial properties. When the amount of silver nitrate used is lower than the lower limit of the range defined by the present invention, small-diameter silver nanoparticles will be formed. Silver nanoparticles with too small a particle size will also agglomerate, resulting in a reduction in specific surface area. The present invention achieves the purpose of regulating the particle size of the silver nanoparticles by controlling the amount of silver nitrate used.
[0055] In some optional examples, after all the silver ammonia solution has been added dropwise, mixing and stirring are continued under heating conditions at 70-80° C. in a water bath for 8-10 hours, for example, 8.0 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9.0 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours or 10.0 hours, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0056] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the dialysis time is 2 to 3 days.
[0058] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional embodiments, the freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] As a preferred technical solution of the present invention, in step (III), the concentration of silver-loaded chitosan in the silver-loaded chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0061] In some optional examples, the mass ratio of the silver-loaded chitosan in the silver-loaded chitosan solution to the montmorillonite is 1:(4-5), for example, 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] The present invention utilizes silver-loaded chitosan to perform intercalation modification on montmorillonite, aiming to enhance the barrier properties of the product, and realize the effective fixation and dispersion of silver-loaded chitosan, thereby preventing the agglomeration of silver nanoparticles. The present invention particularly limits the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution to 1: (4-5), and an appropriate amount of silver-loaded chitosan can significantly improve the barrier properties of the composite film, because montmorillonite is a layered silicate mineral with a large specific surface area and certain barrier properties. However, the interlayer distance in its original structure is limited, and gas molecules can still penetrate through the interlayer channel. After the silver-loaded chitosan is inserted into the montmorillonite interlayer, it can prop up the montmorillonite lamellae to form a more regular intercalation structure, which makes the gas molecules need to pass through the multilayer barrier structure formed by the montmorillonite lamellae and the silver-loaded chitosan along a tortuous path when passing through the film, thereby greatly increasing the gas permeation path length and significantly improving the barrier properties. In addition, the chitosan in the silver-loaded chitosan is rich in carboxymethyl functional groups and amino functional groups, which can form strong hydrogen bond interactions with the hydroxyl groups on the surface of montmorillonite. These interactions not only help to maintain the stable dispersion of the silver-loaded chitosan molecules, but also prevent the silver nanoparticles from agglomerating between montmorillonite layers. The uniformly dispersed silver-loaded chitosan not only improves the utilization rate of the silver nanoparticles, but also enables the silver nanoparticles to more fully contact the external environment, thereby more effectively killing or inhibiting the growth of bacteria and exerting better antibacterial properties in the intercalated montmorillonite.
[0063] When the amount of silver-loaded chitosan exceeds the upper limit of the range of the present invention, it will not only affect the barrier properties of the intercalated montmorillonite, but also affect the antibacterial properties of the intercalated montmorillonite. This is because, for barrier properties, too many silver-loaded chitosan molecules cannot be completely inserted into the interlayer structure of montmorillonite, but tend to accumulate on the surface of montmorillonite or in the interlayer gaps. This accumulation state not only destroys the original layered structure of montmorillonite, but may also cause structural defects due to the disordered arrangement of silver-loaded chitosan molecules. These defects become channels for the penetration of small molecules, thereby reducing the barrier properties of the intercalated montmorillonite. For antibacterial properties, the adsorption sites on the surface of the montmorillonite layer are limited, and the excess silver-loaded chitosan cannot be effectively fixed and is in a relatively free state in the system. The probability of mutual collision between the silver nanoparticles in these unfixed silver-loaded chitosans increases, and it is easier to agglomerate, thereby reducing the dispersibility of the silver-loaded chitosan in the system, and then affecting the antibacterial properties of the intercalated montmorillonite.
[0064] When the amount of silver-loaded chitosan is lower than the lower limit of the range defined in the present invention, the concentration of silver nanoparticles in the intercalated montmorillonite will be insufficient, thereby weakening the antibacterial effect of the intercalated montmorillonite. In addition, the silver-loaded chitosan between the montmorillonite sheets will be sparsely distributed, and the dispersion and fixation of the silver-loaded chitosan by the montmorillonite cannot be fully utilized. At this time, the silver nanoparticles in the silver-loaded chitosan are prone to agglomeration due to the lack of sufficient spatial restrictions and interactions, thereby affecting the antibacterial properties of the intercalated montmorillonite. At the same time, when the amount of silver-loaded chitosan is too low, it means that the amount of montmorillonite is too high, and too much montmorillonite will hinder the release and diffusion of silver nanoparticles to a certain extent, further reducing the antibacterial properties of the intercalated montmorillonite. In addition, the too low amount of silver-loaded chitosan will also cause defects in the internal structure of the intercalated montmorillonite, such as voids and cracks, etc. These defects not only reduce the mechanical properties of the intercalated montmorillonite, but also become the penetration and diffusion channels of small molecules, thereby further reducing the barrier properties of the intercalated montmorillonite.
[0065] In some optional examples, the mixing and stirring time of the silver-loaded chitosan solution and montmorillonite is 5 to 7 hours, for example, it can be 5.0 hours, 5.2 hours, 5.4 hours, 5.6 hours, 5.8 hours, 6.0 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours or 7.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional embodiments, the heating temperature when the silver-loaded chitosan solution and montmorillonite are mixed and stirred is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] As a preferred technical solution of the present invention, in step (IV), the weight proportions of the components in the mixed material are as follows:
[0068] Polylactic acid 78-83 parts;
[0069] 15-20 parts of intercalated montmorillonite;
[0070] 1~2 parts of plasticizer;
[0071] 0.5~1.5 parts of lubricant;
[0072] Antioxidant 0.1~0.5 parts.
[0073] Among them, the weight parts of polylactic acid can be 78 parts, 78.5 parts, 79 parts, 79.5 parts, 80 parts, 80.5 parts, 81 parts, 81.5 parts, 82 parts, 82.5 parts or 83 parts; the weight parts of intercalated montmorillonite can be 15 parts, 15.5 parts, 16 parts, 16.5 parts, 17 parts, 17.5 parts, 18 parts, 18.5 parts, 19 parts, 19.5 parts or 20 parts; the weight parts of plasticizer can be 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts , 1.7 parts, 1.8 parts, 1.9 parts or 2.0 parts; the weight part of the lubricant can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts; the weight part of the antioxidant can be 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts, but are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0074] In some optional examples, the plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof.
[0075] In some optional examples, the lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof.
[0076] In some optional examples, the antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.
[0077] As a preferred technical solution of the present invention, in step (IV), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction.
[0078] In some optional instances, the temperature of the first zone is 150-160°C, for example, it may be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] In some optional instances, the temperature of the second zone is 160-170°C, for example, it may be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] In some optional instances, the temperature of the third zone is 170-180°C, for example, it may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In some optional instances, the temperature of the fourth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In some optional examples, the temperature of the fifth zone is 185-190°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] In some optional examples, the temperature of the sixth zone is 190-195°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] In some optional examples, the temperature of the seventh zone is 200-205°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In some optional examples, the temperature of the eighth zone is 195-200°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some optional instances, the head temperature of the screw extruder is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] In some optional examples, the screw speed of the screw extruder is 200~300rpm, for example, it can be 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] In some optional examples, the film blowing process is carried out in a film blowing machine, and the interior of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction.
[0089] In some optional instances, the temperature of the ninth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] In some optional instances, the temperature of the tenth zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] In some optional instances, the temperature of the eleventh zone is 185-195°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0092] In some optional instances, the temperature of the twelfth zone is 195-205°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In some optional instances, the temperature of the thirteenth zone is 190-200°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C, 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] In some optional examples, the screw speed of the film blowing machine is 100~200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] In some optional examples, the traction speed of the film blowing machine is 5~10m / min, for example, it can be 5.0m / min, 5.5m / min, 6.0m / min, 6.5m / min, 7.0m / min, 7.5m / min, 8.0m / min, 8.5m / min, 9.0m / min, 9.5m / min or 10.0m / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0096] In some optional examples, the blowing ratio of the film blowing machine is 2 to 5, for example, 2, 3, 4 or 5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0097] In a second aspect, the present invention provides an antibacterial high-barrier fruit and vegetable fresh-keeping film prepared by the preparation method described in the first aspect, wherein the antibacterial high-barrier fruit and vegetable fresh-keeping film comprises polylactic acid, intercalated montmorillonite, a plasticizer, a lubricant and an antioxidant.
[0098] Compared with the prior art, the present invention has the following beneficial effects:
[0099] The antibacterial high-barrier fruit and vegetable fresh-keeping film prepared by the present invention has excellent antibacterial properties and barrier properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables, and reduce food waste and loss. Among them, silver-loaded chitosan can destroy the cell structure of bacteria and interfere with its metabolic process, thereby effectively inhibiting the growth of common food spoilage bacteria such as Escherichia coli and Staphylococcus aureus. At the same time, silver ions have broad-spectrum antibacterial properties and are not easy to develop drug resistance, giving the composite film excellent antibacterial properties and effectively extending the shelf life of fruits and vegetables. The present invention intercalates montmorillonite through silver-loaded chitosan, further improving the interlamellar spacing of montmorillonite, thereby forming a more compact and effective barrier barrier in the composite film, reducing oxygen, moisture, etc. from passing through the composite film, and significantly improving the barrier properties of the composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0100] Figure 1 A process flow chart of the preparation of the composite film provided in Examples 1-5 of the present invention;
[0101] Figure 2 This is the infrared spectrum of chitosan used in Example 1 of the present invention;
[0102] Figure 3 This is the infrared spectrum of the carboxymethyl chitosan prepared in Example 1 of the present invention;
[0103] Figure 4 This is the infrared spectrum of the quaternized carboxymethyl chitosan prepared in Example 1 of the present invention;
[0104] Figure 5 This is a scanning electron microscope image of the chitosan used in Example 1 of the present invention;
[0105] Figure 6 This is a scanning electron microscope image of the quaternized carboxymethyl chitosan prepared in Example 1 of the present invention;
[0106] Figure 7 This is a scanning electron microscope image of the silver-loaded chitosan prepared in Example 1 of the present invention;
[0107] Figure 8 This is a transmission electron microscope image of the montmorillonite used in Example 1 of the present invention;
[0108] Fig. 9 This is a transmission electron microscope image of the intercalated montmorillonite prepared in Example 1 of the present invention;
[0109] Fig.10 XRD spectra of montmorillonite, silver-loaded chitosan prepared in Example 1 of the present invention, and intercalated montmorillonite;
[0110] Fig.11 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in the comparative example of the present invention;
[0111] Fig.12 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in Example 1 of the present invention;
[0112] Fig.13 This is a colony diagram obtained in a test of the antibacterial performance of Staphylococcus aureus of the composite film prepared in the comparative example of the present invention;
[0113] Fig.14 This is a colony diagram obtained in the antibacterial performance test of the composite film prepared in Example 1 of the present invention on Staphylococcus aureus;
[0114] Fig.15 The actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in the green vegetable preservation experiment;
[0115] Fig.16 These are actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in a durian preservation experiment. DETAILED DESCRIPTION
[0116] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0117] Example 1
[0118] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0119] (1) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.5, and ball-milled for 5 hours at a rotation speed of 500 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.5, and ball-milled for a second time at a rotation speed of 500 rpm for 6 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;
[0120] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 10 g / L; add a 50 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 50° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.6, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 30 minutes under 50° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;
[0121] (2) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 2 wt% to a silver nitrate solution with a mass fraction of 3 wt%, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.5, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 1 wt% dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;
[0122] The quaternized carboxymethyl chitosan obtained in step (1) is dispersed in deionized water to obtain a chitosan solution with a concentration of 10 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 70° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.6. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 70° C. for 10 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 10,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -40° C. for 24 h to obtain silver-loaded chitosan.
[0123] (3) dispersing the silver-loaded chitosan obtained in step (2) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 10 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4, mixing and stirring at 50° C. for 7 h, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0124] (4) 78 parts of polylactic acid, 20 parts of the intercalated montmorillonite obtained in step (3), 1 part of ethylene glycol, 0.5 parts of calcium stearate and 0.5 parts of antioxidant 1010 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 170°C, the temperature of the fourth zone is 175°C, the temperature of the fifth zone is 185°C, the temperature of the sixth zone is 190°C, the temperature of the seventh zone is 200°C, the temperature of the eighth zone is 195°C, the temperature of the die head is 180°C, and the screw speed is 200 rpm;
[0125] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 175° C., the temperature of the tenth zone is 180° C., the temperature of the eleventh zone is 185° C., the temperature of the twelfth zone is 195° C., and the temperature of the thirteenth zone is 190° C. The screw speed of the film blowing machine is 100 rpm, the traction speed of the film blowing machine is 5 m / min, and the blowing ratio of the film blowing machine is 2. After film blowing, the antibacterial and high-barrier fruit and vegetable fresh-keeping film is obtained.
[0126] Figure 2 , Figure 3 and Figure 4 The infrared spectra of the chitosan used in this embodiment, the carboxymethyl chitosan prepared in this embodiment and the quaternized carboxymethyl chitosan are shown in FIG. Figure 2 In the infrared spectrum of chitosan shown in the figure, 1380cm -1 The corresponding stretching vibration absorption peak of CN. Figure 3 In the infrared spectrum of carboxymethyl chitosan shown in the figure, 1601cm -1 and 1415cm -1 The antisymmetric and symmetric stretching vibration absorption peaks of the carboxymethyl functional group appeared at 1131 cm -1 and 1059cm -1 The stretching vibration absorption peak of COC appeared at , which indicated that the carboxymethyl functional group was successfully connected to the molecular chain of chitosan.
[0127] exist Figure 4 In the infrared spectrum of quaternized carboxymethyl chitosan shown in the figure, 1478 cm -1The bending vibration absorption peak of CH of the quaternary ammonium functional group appeared at 1598 cm -1 The CN stretching vibration absorption peak of the quaternary ammonium functional group appeared at 1112 cm -1 and 1063cm -1 The stretching vibration absorption peak of the ether group CO appeared at , which indicated that the quaternary ammonium functional group was successfully connected to the molecular chain of carboxymethyl chitosan.
[0128] Figure 5 , Figure 6 and Figure 7 The scanning electron micrographs of the chitosan used in this embodiment, the quaternized carboxymethyl chitosan prepared in this embodiment, and the silver-loaded chitosan are shown in FIG. Figure 5 It can be seen that the chitosan particles have a compact structure and a smooth surface. Figure 6 It can be seen that quaternized carboxymethyl chitosan has a relatively loose molecular structure, and its surface is mainly composed of stacked spherical particles. This is because the carboxymethyl functional groups and quaternary ammonium functional groups introduced into the chitosan molecules enhance the intramolecular interaction force, which is conducive to the large-space curling of its own double helix structure. Figure 7 It can be seen that the surface of silver-loaded chitosan is rough, and a large number of silver nanoparticles are uniformly loaded on the chitosan.
[0129] Figure 8 and Fig. 9 The transmission electron microscope images of the montmorillonite used in this embodiment and the intercalated montmorillonite prepared in this embodiment are shown in Figure 1. Compared with montmorillonite, the interlayer spacing of the intercalated montmorillonite is significantly increased, and the silver-loaded chitosan is evenly dispersed in the intercalated montmorillonite sheets. Fig. 9 It is clear that silver nanoparticles are dispersed between the intercalated montmorillonite layers.
[0130] Fig.10 The XRD spectra of silver-loaded chitosan, montmorillonite and intercalated montmorillonite prepared in this embodiment show that within the range of 2θ of 4 to 10°, silver-loaded chitosan has no obvious diffraction peak, while montmorillonite has obvious diffraction peaks within this angle range. According to the Bragg equation, the interlayer spacing of montmorillonite can be calculated to be 1.501nm. The characteristic diffraction peak of intercalated montmorillonite obtained after intercalation modification moves to 2θ=5.30°, and the interlayer spacing at this time increases from the initial 1.501nm to 1.665nm, which indicates that silver-loaded chitosan enters the interlamellar space of montmorillonite, increases the interlayer spacing of montmorillonite, and forms an intercalated composite material.
[0131] Example 2
[0132] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. Figure 1As shown, the preparation method specifically comprises the following steps:
[0133] (1) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.8, and ball-milled for 4.8 hours at a rotation speed of 520 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.2, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.55, and ball-milled for a second time at a rotation speed of 520 rpm for 5.8 hours to obtain a solid product; the solid product was mixed with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8.5 wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;
[0134] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 12 g / L; add a 52 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 52° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.62, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 28 minutes under 52° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.05, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;
[0135] (2) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 2.5 wt % to a silver nitrate solution with a mass fraction of 3.5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.6, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 1.5 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;
[0136] The quaternized carboxymethyl chitosan obtained in step (1) is dispersed in deionized water to obtain a chitosan solution with a concentration of 12 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 72° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.62. After all the silver ammonia solution is dripped, the mixture is stirred under heating in a water bath at 72° C. for 9.5 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 12,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -42° C. for 21 h to obtain silver-loaded chitosan.
[0137] (3) dispersing the silver-loaded chitosan obtained in step (2) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 12 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.2, mixing and stirring at 52° C. for 6.5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0138] (4) 80 parts of polylactic acid, 16 parts of intercalated montmorillonite obtained in step (3), 2 parts of epoxidized soybean oil, 1.5 parts of paraffin wax and 0.5 parts of antioxidant 1076 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 152° C., the temperature of the second zone is 162° C., the temperature of the third zone is 172° C., the temperature of the fourth zone is 178° C., the temperature of the fifth zone is 186° C., the temperature of the sixth zone is 191° C., the temperature of the seventh zone is 201° C., the temperature of the eighth zone is 196° C., the head temperature is 182° C., and the screw speed is 220 rpm;
[0139] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 178° C., the temperature of the tenth zone is 182° C., the temperature of the eleventh zone is 188° C., the temperature of the twelfth zone is 198° C., and the temperature of the thirteenth zone is 192° C. The screw speed of the film blowing machine is 120 rpm, the traction speed of the film blowing machine is 6 m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the antibacterial and high-barrier fruit and vegetable fresh-keeping film is obtained.
[0140] Example 3
[0141] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0142] (1) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4, and ball-milled for 4.5 hours at a rotation speed of 550 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.5, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.6, and ball-milled for a second time at a rotation speed of 550 rpm for 5.5 hours to obtain a solid product; the solid product was mixed with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;
[0143] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 15 g / L; add a 55 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 55° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.65, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 25 minutes under 55° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.1, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;
[0144] (2) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 3 wt % to a silver nitrate solution with a mass fraction of 4 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.6, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 2 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;
[0145] The quaternized carboxymethyl chitosan obtained in step (1) is dispersed in deionized water to obtain a chitosan solution with a concentration of 15 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 75° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.65. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 75° C. for 9 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 15,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -45° C. for 18 h to obtain silver-loaded chitosan.
[0146] (3) dispersing the silver-loaded chitosan obtained in step (2) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 15 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.5, mixing and stirring at 55° C. for 6 h, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0147] (4) 81 parts of polylactic acid, 16 parts of intercalated montmorillonite obtained in step (3), 1.5 parts of pentaerythritol, 1.2 parts of glyceryl monostearate and 0.3 parts of antioxidant DSTP are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 155° C., the temperature of the second zone is 165° C., the temperature of the third zone is 175° C., the temperature of the fourth zone is 180° C., the temperature of the fifth zone is 187° C., the temperature of the sixth zone is 192° C., the temperature of the seventh zone is 202° C., the temperature of the eighth zone is 197° C., the head temperature is 185° C., and the screw speed is 250 rpm;
[0148] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 180° C., the temperature of the tenth zone is 185° C., the temperature of the eleventh zone is 190° C., the temperature of the twelfth zone is 200° C., and the temperature of the thirteenth zone is 195° C. The screw speed of the film blowing machine is 150 rpm, the traction speed of the film blowing machine is 7 m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the antibacterial and high-barrier fruit and vegetable fresh-keeping film is obtained.
[0149] Example 4
[0150] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0151] (1) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.2, and ball-milled for 4.2 hours at a rotation speed of 580 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.8, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.65, and ball-milled for 5.2 hours at a rotation speed of 580 rpm to obtain a solid product; the solid product was mixed with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9.5wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;
[0152] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 18 g / L; add a dimethyl diallyl ammonium chloride solution with a mass fraction of 58 wt% to the carboxymethyl chitosan solution under continuous stirring and 58° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.68, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 22 minutes under 58° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.15, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;
[0153] (2) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 3.5 wt % to a silver nitrate solution with a mass fraction of 4.5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.7, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 2.5 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;
[0154] The quaternized carboxymethyl chitosan obtained in step (1) is dispersed in deionized water to obtain a chitosan solution with a concentration of 18 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 78° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.68. After all the silver ammonia solution is dripped, the mixture is stirred under heating in a water bath at 78° C. for 8.5 h. The reaction product is then dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 18,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -48° C. for 15 h to obtain silver-loaded chitosan.
[0155] (3) dispersing the silver-loaded chitosan obtained in step (2) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 18 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.8, mixing and stirring at 58° C. for 5.5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0156] (4) 80 parts of polylactic acid, 18 parts of intercalated montmorillonite obtained in step (3), 1 part of polyvinyl alcohol, 0.5 parts of glyceryl distearate and 0.5 parts of antioxidant 168 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 158°C, the temperature of the second zone is 168°C, the temperature of the third zone is 178°C, the temperature of the fourth zone is 182°C, the temperature of the fifth zone is 188°C, the temperature of the sixth zone is 193°C, the temperature of the seventh zone is 203°C, the temperature of the eighth zone is 198°C, the temperature of the die head is 188°C, and the screw speed is 280 rpm;
[0157] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 182° C., the temperature of the tenth zone is 188° C., the temperature of the eleventh zone is 192° C., the temperature of the twelfth zone is 202° C., and the temperature of the thirteenth zone is 198° C. The screw speed of the film blowing machine is 180 rpm, the traction speed of the film blowing machine is 8 m / min, and the blowing ratio of the film blowing machine is 4. After film blowing, the antibacterial and high-barrier fruit and vegetable fresh-keeping film is obtained.
[0158] Example 5
[0159] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0160] (1) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.5, and ball-milled for 4 hours at a speed of 600 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:4, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.7, and ball-milled for a second time at a speed of 600 rpm for 5 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 10 wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain carboxymethyl chitosan;
[0161] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 20 g / L; add a 60 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 60° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.7, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 20 minutes under 60° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.2, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;
[0162] (2) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 4 wt % to a silver nitrate solution with a mass fraction of 5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.8, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding a 3 wt % ammonia solution to the silver oxide suspension until the black silver oxide precipitate is completely dissolved, thereby obtaining a clear silver ammonia solution;
[0163] The quaternized carboxymethyl chitosan obtained in step (1) is dispersed in deionized water to obtain a chitosan solution with a concentration of 20 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 80° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.7. After all the silver ammonia solution is dripped in, the mixture is mixed and stirred for 8 h under heating in a water bath at 80° C., and then the reaction product is dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 20,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -50° C. for 12 h to obtain silver-loaded chitosan;
[0164] (3) dispersing the silver-loaded chitosan obtained in step (2) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 20 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:5, mixing and stirring at 60° C. for 5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;
[0165] (4) 83 parts of polylactic acid, 15 parts of intercalated montmorillonite obtained in step (3), 1 part of triacetin, 0.9 parts of zinc stearate and 0.1 parts of antioxidant 691 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 160°C, the temperature of the second zone is 170°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 185°C, the temperature of the fifth zone is 190°C, the temperature of the sixth zone is 195°C, the temperature of the seventh zone is 205°C, the temperature of the eighth zone is 200°C, the temperature of the die head is 190°C, and the screw speed is 300 rpm;
[0166] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 185° C., the temperature of the tenth zone is 190° C., the temperature of the eleventh zone is 195° C., the temperature of the twelfth zone is 205° C., and the temperature of the thirteenth zone is 200° C. The screw speed of the film blowing machine is 200 rpm, the traction speed of the film blowing machine is 10 m / min, and the blowing ratio of the film blowing machine is 5. After film blowing, the antibacterial and high-barrier fruit and vegetable fresh-keeping film is obtained.
[0167] Example 6
[0168] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, which differs from Embodiment 1 in that, in step (1), the mass ratio of chitosan powder to sodium chloroacetate is adjusted to 1:2, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0169] Example 7
[0170] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, which differs from Embodiment 1 in that, in step (1), the mass ratio of chitosan powder to sodium chloroacetate is adjusted to 1:5, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0171] Example 8
[0172] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, which is different from Embodiment 1 in that, in step (1), the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is adjusted to 1:0.5, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0173] Example 9
[0174] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, which is different from Embodiment 1 in that, in step (1), the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is adjusted to 1:0.8, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0175] Example 10
[0176] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. The difference from Embodiment 1 is that in step (3), the mass ratio of quaternized carboxymethyl chitosan to silver nitrate is adjusted to 1:0.5, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0177] Embodiment 11
[0178] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film, which differs from Embodiment 1 in that, in step (3), the mass ratio of quaternized carboxymethyl chitosan to silver nitrate is adjusted to 1:0.8, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0179] Example 12
[0180] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. The difference from Embodiment 1 is that in step (4), the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution is adjusted to 1:3, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0181] Example 13
[0182] This embodiment provides a method for preparing an antibacterial and high-barrier fruit and vegetable fresh-keeping film. The difference from Embodiment 1 is that in step (4), the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution is adjusted to 1:6, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0183] Comparative Example
[0184] This comparative example provides a method for preparing a composite film. The difference from Example 1 is that steps (1) to (3) are omitted, intercalated montmorillonite is not added to the mixed material, and the weight proportions of the other components are as follows:
[0185] Polylactic acid 97 parts;
[0186] 1 part of ethylene glycol;
[0187] 1.5 parts of calcium stearate;
[0188] Antioxidant 10100.5 parts;
[0189] Other process parameters and operation steps are exactly the same as those in Example 1.
[0190] Application Examples
[0191] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on green vegetables. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other cartons. Two bunches of green vegetables with similar freshness and the same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The condition of the green vegetables was observed and photographed every two days. Fig.15 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store green vegetables can keep the green vegetables extremely fresh on the 8th day of storage, effectively inhibit the water loss of the green vegetables, maintain the color of the green vegetables, maintain the quality during storage, and extend the shelf life.
[0192] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on durian. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other cartons. Two durians of similar freshness and same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The state of the durians was observed and photographed every two days. Fig.16 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store durian can keep the durian very fresh on the 8th day of storage, effectively inhibit the opening, rotting and deterioration of the durian, maintain its quality during storage, and extend its shelf life.
[0193] The antibacterial properties and barrier properties of the composite films prepared in Examples 1-13 and the comparative example were tested, and the test method was as follows:
[0194] (1) Antibacterial properties:
[0195] The antibacterial properties of the composite films provided in Example 1 and the comparative example were analyzed by the antibacterial zone method. The composite films provided in Example 1 and the comparative example were first cut into discs with a diameter of 6 mm and uniform size. Then 100 μL of a 10 6CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were evenly spread on the surface of the nutrient agar medium plate. The cut film samples were placed on the surface of the nutrient agar medium plate coated with the bacterial solution, and then placed in a 37℃ constant temperature box for 24 hours. The size of the antibacterial zone around the film sample was observed and photographed and recorded, and the following was obtained: Fig.11 , Fig.12 , Fig.13 and Fig.14 Colony images are shown.
[0196] Fig.11 and Fig.12 The colony images of the composite films prepared in the comparative example and in Example 1 are obtained in the antibacterial performance test of Escherichia coli. It can be seen from the comparison that there is almost no antibacterial zone around the composite film prepared in the comparative example, while there is an obvious antibacterial zone around the composite film prepared in Example 1, which indicates that the composite film prepared in the present invention has excellent antibacterial ability against Escherichia coli.
[0197] Fig.13 and Fig.14 The colony images are respectively obtained in the antibacterial performance test of Staphylococcus aureus of the composite films prepared by the comparative example and Example 1 of the present invention. It can be seen from the comparison that there is almost no antibacterial zone around the periphery of the composite film prepared by the comparative example, and there is an obvious antibacterial zone around the periphery of the composite film prepared by Example 1, which indicates that the composite film prepared by the present invention has excellent antibacterial ability against Staphylococcus aureus.
[0198] (2) Antibacterial properties:
[0199] The antibacterial activity of the composite films provided in Examples 1-13 was analyzed by colony counting method. The composite films provided in Examples 1-13 and the comparative example were cut into 3 mm×3 mm square film samples. 100 μL of 10 6 CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were dispersed on the surface of the film sample and cultured at 37°C for 12 hours to obtain the sample; then 1500μL of PBS solution was used to wash the bacteria from the sample surface, and 20μL of PBS solution was taken and dispersed on the nutrient agar plate, and cultured at 37°C for 12 hours, after which the surviving colonies were counted. The antibacterial rate (%) was calculated using the following formula:
[0200]
[0201] Wherein, X is the number of colonies on the composite film sample provided in the comparative example, and Y is the number of colonies on the composite film sample provided in Examples 1-13.
[0202] (3) Barrier properties:
[0203] The barrier properties of the composite films provided in Examples 1-13 and the comparative examples were characterized by water vapor permeability. The water vapor permeability was measured in a constant temperature and humidity chamber according to GB / T 1037-2021 “Determination of Water Vapor Permeability of Plastic Films and Sheets by Cup Weight Gain and Weight Loss Method”. The experimental conditions were: temperature 38±0.6°C, relative humidity 90%±2%.
[0204] Table 1
[0205] <![CDATA[Water vapor transmission rate g / (m 2 ·24h)]]> E. coli antibacterial rate% Antibacterial rate of Staphylococcus aureus % Example 1 11.8 96.8 95.2 Example 2 11.3 97.2 95.8 Example 3 10.5 97.8 96.3 Example 4 9.8 98.6 96.7 Example 5 9.2 99.3 97.4 Example 6 23.6 85.7 83.5 Example 7 17.2 92.8 90.6 Example 8 25.4 83.2 81.0 Example 9 15.3 90.5 88.9 Example 10 18.4 70.1 67.2 Embodiment 11 16.3 78.3 76.5 Example 12 30.7 81.9 80.1 Example 13 21.9 72.8 71.3 Comparative Example 52.6 — —
[0206] It can be seen from the test data provided in Table 1 that the composite films provided in Examples 1-5 of the present invention have excellent antibacterial properties and barrier properties.
[0207] It can be seen from the test data of Example 1, Example 6 and Example 7 that excessive or insufficient dosage of sodium chloroacetate will directly affect the carboxymethylation modification effect of chitosan and the subsequent quaternization modification effect, thereby affecting the antibacterial and barrier properties of the composite film.
[0208] It can be seen from the test data of Example 1, Example 8 and Example 9 that too high or too low a dosage of dimethyldiallylammonium chloride will directly affect the quaternization modification effect of carboxymethyl chitosan and the subsequent intercalation modification effect of montmorillonite, thereby affecting the antibacterial properties and barrier properties of the composite film.
[0209] It can be seen from the test data of Example 1, Example 10 and Example 11 that excessively high or low dosage of silver nitrate directly affects the loading amount of silver nanoparticles in the silver-loaded chitosan, thereby affecting the antibacterial and barrier properties of the composite film.
[0210] It can be seen from the test data of Example 1, Example 12 and Example 13 that too high or too low a dosage of montmorillonite directly affects the intercalation modification effect of montmorillonite, thereby affecting the antibacterial and barrier properties of the composite film.
[0211] It can be seen from the test data of Example 1 and the comparative example that the present invention can significantly improve the antibacterial property and barrier property of the polylactic acid composite film by adding intercalated montmorillonite into the composite film.
[0212] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an antibacterial high-barrier fruit and vegetable fresh-keeping film, characterized in that: The preparation method comprises: (I) ball-milling chitosan powder and sodium hydroxide to obtain a mixture, adding sodium chloroacetate and sodium iodide to the mixture for a second ball-milling to obtain carboxymethyl chitosan; then, quaternizing the carboxymethyl chitosan with dimethyl diallyl ammonium chloride to obtain quaternized carboxymethyl chitosan; (II) dispersing the quaternized carboxymethyl chitosan obtained in step (I) in deionized water to obtain a chitosan solution, dripping a silver ammonia solution into the chitosan solution under stirring and water bath heating conditions, and continuing to mix, stir and heat to react after all the silver ammonia solution has been dripped in, and then dialyzing and freeze-drying to obtain silver-loaded chitosan; (III) dispersing the silver-loaded chitosan obtained in step (II) in deionized water to obtain a silver-loaded chitosan solution, adding montmorillonite to the silver-loaded chitosan solution, mixing, stirring and heating, and then filtering, washing and drying to obtain intercalated montmorillonite; (IV) The polylactic acid, the intercalated montmorillonite obtained in step (III), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixed material, and the mixed material is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the antibacterial and high-barrier fruit and vegetable fresh-keeping film.
2. The preparation method according to claim 1, characterized in that: In step (I), the mass ratio of chitosan powder to sodium hydroxide is 1:(3.5-4.5); The rotation speed of the first ball mill is 500-600 rpm; The time of the first ball milling is 4 to 5 hours; The mass ratio of the chitosan powder to sodium chloroacetate is 1:(3-4); The mass ratio of the sodium chloroacetate to the sodium iodide is 1:(0.5-0.7); The rotation speed of the secondary ball milling is 500-600 rpm; The secondary ball milling time is 5 to 6 hours; The preparation process of the carboxymethyl chitosan also includes: After the secondary ball milling, a solid product is obtained, and the solid product is mixed evenly with deionized water to obtain a product solution. A hydrochloric acid solution with a mass fraction of 8-10wt% is added to the product solution to adjust the pH value of the product solution to 7; then, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan.
3. The preparation method according to claim 1, characterized in that: In step (I), the quaternized carboxymethyl chitosan is prepared by the following method: The carboxymethyl chitosan is dissolved in deionized water and mixed evenly to obtain a carboxymethyl chitosan solution; under continuous stirring and water bath heating conditions, a dimethyl diallyl ammonium chloride solution is added dropwise to the carboxymethyl chitosan solution, and after the dimethyl diallyl ammonium chloride solution is completely added dropwise, the mixture is continuously stirred and heated to obtain a reaction product; acetone is added to the reaction product, and white floccules are generated after mixing, and then the mixture is filtered, washed and dried to obtain the quaternized carboxymethyl chitosan.
4. The preparation method according to claim 3, characterized in that: The concentration of carboxymethyl chitosan in the carboxymethyl chitosan solution is 10-20 g / L; The mass fraction of the dimethyldiallylammonium chloride solution is 50-60wt%; During the process of dropwise adding the dimethyldiallylammonium chloride solution, the water bath heating temperature is 50-60° C.; The mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:(0.6-0.7); After all the dimethyldiallylammonium chloride solution has been added dropwise, continue to mix and stir in a water bath at 50-60° C. for 20-30 minutes; The volume ratio of the reaction product to the acetone is 1:(1-1.2).
5. The preparation method according to claim 1, characterized in that: In step (II), the silver ammonia solution is prepared by the following method: Under stirring conditions, adding a sodium hydroxide solution to the silver nitrate solution to react and generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution dropwise to the silver oxide suspension until the black silver oxide precipitate is completely dissolved to obtain a clear silver ammonia solution; The mass fraction of the silver nitrate solution is 3-5wt%; The mass fraction of the sodium hydroxide solution is 2-4wt%; The mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:(0.5-0.8); The concentration of the ammonia solution is 1-3 wt %.
6. The preparation method according to claim 1, characterized in that: In step (II), the concentration of quaternized carboxymethyl chitosan in the chitosan solution is 10-20 g / L; During the process of adding the silver ammonia solution dropwise, the water bath is heated at a temperature of 70-80° C.; The mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:(0.6-0.7); After all the silver ammonia solution has been added, continue to mix and stir in a water bath at 70-80° C. for 8-10 hours; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 2 to 3 days; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 12 to 24 hours.
7. The preparation method according to claim 1, characterized in that: In step (III), the concentration of silver-loaded chitosan in the silver-loaded chitosan solution is 10-20 g / L; The mass ratio of the silver-loaded chitosan in the silver-loaded chitosan solution to the montmorillonite is 1:(4-5); The mixing and stirring time of the silver-loaded chitosan solution and montmorillonite is 5 to 7 hours; The heating temperature when the silver-loaded chitosan solution and montmorillonite are mixed and stirred is 50-60°C.
8. The preparation method according to claim 1, characterized in that: In step (IV), the weight proportions of the components in the mixed material are as follows: Polylactic acid 78-83 parts; 15-20 parts of intercalated montmorillonite; 1~2 parts of plasticizer; 0.5~1.5 parts of lubricant; Antioxidant 0.1~0.5 parts; The plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof; The lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof; The antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.
9. The preparation method according to claim 1, characterized in that: In step (IV), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction; The temperature of the first zone is 150-160°C; The temperature of the second zone is 160-170°C; The temperature of the third zone is 170-180°C; The temperature of the fourth zone is 175-185°C; The temperature of the fifth zone is 185-190°C; The temperature of the sixth zone is 190-195°C; The temperature of the seventh zone is 200-205°C; The temperature of the eighth zone is 195-200°C; The head temperature of the screw extruder is 180-190°C; The screw speed of the screw extruder is 200-300 rpm; The film blowing process is carried out in a film blowing machine, and the inside of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction; The temperature of the ninth zone is 175-185°C; The temperature of the tenth zone is 180-190°C; The temperature of the eleventh zone is 185-195°C; The temperature of the twelfth zone is 195-205°C; The temperature of the thirteenth zone is 190-200°C; The screw speed of the film blowing machine is 100-200 rpm; The traction speed of the film blowing machine is 5-10 m / min; The blowing ratio of the film blowing machine is 2-5.
10. An antibacterial high-barrier fruit and vegetable fresh-keeping film prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The antibacterial and high-barrier fruit and vegetable fresh-keeping film comprises polylactic acid, intercalated montmorillonite, a plasticizer, a lubricant and an antioxidant.
Citation Information
Cited By
Slow-release antibacterial composite dispersion as well as preparation method and application thereof
CN121040517A